Study on the Soil Strength and Density Relationships of Latosol and Red Yellow Podzolic Soils - Asep Sapei; E. Namaken Sembiring; Gatot Pramuhadi (PERTETA, 2000)
The soil strength characteristic, which is usually e.xpressed bycohesion and internal piction, is as basic data for applying farmmachineries/equipments and farm structures. The objective of this research is to study the soil strength and density relationships of latosol and red yellowish podzolic soil. This research was conducted by standard compaction test and soil strength test (uniaxial, direct shear and triaxiul).